2023
DOI: 10.1007/s40847-023-00240-5
|View full text |Cite
|
Sign up to set email alerts
|

Digital infrastructural development and inclusive growth in Sub-Saharan Africa

Abstract: The study assesses the effect of digital infrastructural development on inclusive growth in 44 Sub-Saharan African countries from 2000 to 2020. The study adopts the Driscoll-Kraay strategy to address cross-sectional dependence and the Newey-West standard errors to address errors-related problems. The study adopted the four indicators of digital infrastructures and their component score to determine their effect on inclusive growth which ensures equitable distribution of resources in an economy. The findings of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…This finding, therefore, requires the governments in Central, Eastern, Southern and Western Africa to promote usage and improve investment in digital infrastructure that benefits all. Kouladoum (2023) and Oyinlola and Adedeji (2022) arrived at similar conclusions regarding the need for governments to invest more in digital infrastructure development.…”
Section: Evidence From Africamentioning
confidence: 65%
“…This finding, therefore, requires the governments in Central, Eastern, Southern and Western Africa to promote usage and improve investment in digital infrastructure that benefits all. Kouladoum (2023) and Oyinlola and Adedeji (2022) arrived at similar conclusions regarding the need for governments to invest more in digital infrastructure development.…”
Section: Evidence From Africamentioning
confidence: 65%
“…This digital divide represents a significant human and economic loss for cities and territories in Africa, and research has shown that the number of Internet users positively affects the inclusive growth of economies (Abdychev et al, 2020; Ndubuisi et al, 2021; Kouladoum, 2023), which can be characterized as both spatial and socioeconomic (Nijman and Wei, 2020). Indeed, the deployment of digital infrastructure reproduces spatial inequalities, thus enriching the multiscale spatial divide between cities and peripheries, metropolises and secondary cities, cities, and rural areas, as well as developed and less developed countries (Ramalingam, 2016; UNESCO, 2016; Otioma et al, 2019).…”
Section: Societal Impacts Of the Deployment Of Digital Technologies I...mentioning
confidence: 99%
“…In addition, industrialization and growth also have a positive impact on infrastructure development, however, there is no significant impact of infrastructural development in the region. Kouladoum (2023) analysed the impact of the inclusive growth aspect of digital infrastructure development in Sub-Saharan African economies for 20 years using the Driscoll-Kraay strategy and Newey-West standard errors on four indicators of digital infrastructure. The findings of the study revealed that mobile cellular subscriptions per 100 adults, the number of fixed broadband subscribers, fixed telephone and the number of individuals using the internet have a positive and significant impact on the inclusive growth of the region.…”
Section: Transport Infrastructure and Gender Inequalitymentioning
confidence: 99%